Advances in nonpharmacologic therapies for ventricular arrhythmias. Issue 1 (January 2006) - Marinskis, Germanas; Aidietis, Audrius
Ventricular tachycardias differ in their clinical course and prognosis, as this group includes arrhythmias of diverse etiologies. Idiopathic ventricular tachycardias have good prognosis and catheter ablation is an alternative for long-term antiarrhythmic drug treatment. In some patients, sophisticated mapping systems and approaches (pericardial and surgical) have to be used. Ventricular tachycardias related to structural heart disease are more difficult to ablate due to the diffuse character of underlying disease and in most cases with ventricular dysfunction, an option to use an implantable cardioverter––defibrillator should be considered. Recent studies have shown that implantable cardioverter––defibrillators are the only effective option for secondary prevention of sudden cardiac death. Primary prevention of sudden cardiac death is most effective when an implantable cardioverter––defibrillator is implanted; however, this approach is costly and needs elaborating criteria for risk stratification. Optimal treatment of underlying heart disease and correction of risk factors will help to decrease the number of patients suffering from VTs and dying suddenly.